The three-century journey so far: internal attribution factors influencing consumer solid waste disposal in terrestrial ecosystem destruction - Yeboah, Abraham; Addae, Ebenezer Kwame; Owusu-Prempeh, Vida; Kumi, Ernest; Agyekum, Ofosu (Frontiers in Sustainability, 2025)
Open and unsanitary solid waste disposal are major problems causing the drastic depletion of terrestrial ecosystems that have never occurred before in human social life. The internal attribution factors from the attribution theory were used to assess the terrestrial ecosystem destruction caused by consumers’ solid waste disposal. With empirical data from 727 respondents selected conveniently, analysis was made using covariance-based structural equation modeling (CB-SEM). The study found that consumers’ negative attitude of ability and effort significantly influenced terrestrial ecosystem destruction among consumers’ solid waste disposal, while temperament was insignificant. The cultural space as a mediator was positively and significantly related to terrestrial ecosystem destruction. Again, consumer embodiment as a moderator was positively and significantly related to ecosystem destruction. The results and their proposed practical implications provide great insights into terrestrial ecosystem destruction among consumers’ solid waste disposal.